Excited states of diphenylacetylene (tolan): Near and vacuum UV polarization spectroscopy - Nguyen, Duy Duc; Jones, Nykola C.; Hoffmann, Søren Vrønning; Spanget-Larsen, Jens (European Journal of Chemistry, 2024)
The UV absorbance spectrum of the important chromophore diphenylacetylene (tolan) is investigated by Synchrotron Radiation Linear Dichroism (SRLD) spectroscopy using stretched polyethylene as an anisotropic solvent. The investigation covers the range of 58,000-28,000 cm–1 (172-360 nm). The observed linear dichroism provides information on the transition moment directions of the four main absorbance bands A, B, C, and D at 33,300, 44,400, 51,000, and 57,000 cm-1 (300, 225, 196, and 175 nm). The experimental wavenumbers, intensities, and polarization directions are compared with the results of quantum chemical calculations using the semiempirical all-valence-electrons method Linear Combination of Orthogonalized Atomic Orbitals (LCOAO) and Time-Dependent Density Functional Theory (TD-DFT) with the functional CAM-B3LYP. Magnetic Circular Dichroism (MCD) B-terms predicted with LCOAO suggest that a number of optically weak transitions may be observed by MCD spectroscopy.